Solving Rubik's Cube: Disk Is the New RAM. - Kunkle, Daniel; Cooperman, Gene (Communications of the ACM, 2008)
The article focuses on disk-based computation, an effort to make use of parallel disks in scientific computation. It has reached the mainstream media in 2007 when its proponents showed that Rubik's Cube can be solved in 26 moves or less. Proponents used Rubik's Cube because it is an example of a large enumeration problem for which disk-based computation may lead to breakthroughs in several problem domains including group theory, hardware and software verification and coding theory. After limiting the study to 4 GB of main memory per computer, researchers performed an overall search for possible configurations and analyzed several possible algorithms. They conclude that disk-based computation enable solutions to problems that require even pentabytes of memory.